Gothic tales - Doyle, Arthur Conan 1859-1930 (Oxford University Press, 2016)
There was a rumour, too, that he was a devil-worshipper, or something of that sort, and also that he had the evil eye...' Arthur Conan Doyle was the greatest genre writer Britain has ever produced. Throughout a long writing career, he drew on his own medical background, his travels, and his increasing interest in spiritualism and the occult to produce a spectacular array of Gothic Tales. Many of Doyle's writings are recognized as the very greatest tales of terror. They range from hauntings in the polar wasteland to evil surgeons and malevolent jungle landscapes. This collection brings together over thirty of Conan Doyle's best Gothic Tales. Darryl Jones's introduction discusses the contradictions in Conan Doyle's very public life - as a medical doctor who became obsessed with the spirit world, or a British imperialist drawn to support Irish Home Rule - and shows the ways in which these found articulation in that most anxious of all literary forms, the Gothic